2016
DOI: 10.1007/s11606-016-3668-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Spiritual Coping and Survival in Patients with HIV

Abstract: BACKGROUND: Studies of spirituality in initially healthy people have shown a survival advantage, yet there are fewer research studies in the medically ill, despite the widespread use of spirituality/religiousness to cope with serious physical illness. In addition, many studies have used limited measures such as religious service attendance. OBJECTIVE: We aimed to examine if, independent of medication adherence, the use of spirituality/religiousness to cope with HIV predicts survival over 17 years. DESIGN: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 39 publications
(46 reference statements)
0
42
1
2
Order By: Relevance
“…Safara et al in their study showed that spirituality can improve one's mental health (19). Furthermore, spiritualityand religion-based practices can empower people in the face of adversities and lifethreatening diseases (20). In addition, based on the findings of a study performed by Tuttle and Davis on the effects of spirituality and religion on marital life, spiritual-religious beliefs can enhance marital satisfaction and happiness, and improve couples' relationships (21).…”
Section: Introductionmentioning
confidence: 99%
“…Safara et al in their study showed that spirituality can improve one's mental health (19). Furthermore, spiritualityand religion-based practices can empower people in the face of adversities and lifethreatening diseases (20). In addition, based on the findings of a study performed by Tuttle and Davis on the effects of spirituality and religion on marital life, spiritual-religious beliefs can enhance marital satisfaction and happiness, and improve couples' relationships (21).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, NRC has been associated with deleterious outcomes [ 18 – 20 ]. Studies have also shown that, in individuals coping with long-term conditions, religious coping may influence mental health, health-related quality of life (HRQoL), treatment adherence, or even survival [ 20 – 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…As regards sexual orientation, heterosexual patients scored more highly in spirituality compared with homosexual patients. In recent studies, it can be observed that spirituality has helped PLHIV to cope with HIV (Ironson, Kremer, & Lucette, 2016;Pecoraro et al, 2016). Other studies have indeed shown that spirituality is a resource used to overcome the challenges presented by HIV (Hussen et al, 2014;Szaflarski, 2013).…”
Section: Discussionmentioning
confidence: 99%